2019
DOI: 10.1001/jamainternmed.2019.3451
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Out-of-Network Billing for Privately Insured Patients Receiving Care in In-Network Hospitals

Abstract: IMPORTANCE Although surprise medical bills are receiving considerable attention from lawmakers and the news media, to date there has been little systematic study of the incidence and financial consequences of out-of-network billing.OBJECTIVE To examine out-of-network billing among privately insured patients with an inpatient admission or emergency department (ED) visit at in-network hospitals. DESIGN, SETTING, AND PARTICIPANTSA retrospective analysis using data from the Clinformatics Data Mart database (Optum)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 24 publications
3
69
2
Order By: Relevance
“…Second, many Marketplace plans have narrow provider networks, 33,34 leaving some enrollees with large medical bills for out-of-network care, or compelling others to delay or forgo care when innetwork providers are inaccessible. 35,36 Third, since Marketplace plan enrollees had lower rates of continuous coverage, health care costs incurred during gaps in coverage 37 could have increased their financial strain. 20 Given that dental coverage is not mandated as an essential health benefit in either Medicaid or Marketplace plans, [38][39][40] predictably, enrollees from both plans had equal difficulty affording dental care in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many Marketplace plans have narrow provider networks, 33,34 leaving some enrollees with large medical bills for out-of-network care, or compelling others to delay or forgo care when innetwork providers are inaccessible. 35,36 Third, since Marketplace plan enrollees had lower rates of continuous coverage, health care costs incurred during gaps in coverage 37 could have increased their financial strain. 20 Given that dental coverage is not mandated as an essential health benefit in either Medicaid or Marketplace plans, [38][39][40] predictably, enrollees from both plans had equal difficulty affording dental care in our study.…”
Section: Discussionmentioning
confidence: 99%
“…That is, more than 4 in 10 trips to the ER led to patients getting surprise medical bills. 137 A recent study found that out-of-network billing by these medical specialists raises physician payments for privately insured patients and raises health care spending by $40 billion annually. 138 Hospital outsourcing of emergency, radiology, anesthesiology, and other departments has provided an opening for physician practices to operate these services as independent organizations.…”
Section: Surprise Medical Billing Emergency Services and Physician mentioning
confidence: 99%
“…But, consider the practice of "surprise billing"; one study indicated that 40% of emergency department patients and inpatients received out-of-network bills for care delivered at in-network settings. 5 Not only has this practice, which is widely perceived to be unfair, drawn the attention of regulators, but it has been shown to lead to widespread mistrust of the medical system as a whole and, even more disturbing, to the avoidance of seeking care by patients. 6 Notably, all of these examples have effects that stretch far beyond any one organization because they affect individuals, institutions, entire classes of organizations, the health system as a whole and, crucially, patient health.…”
Section: A Diversity Of Breaches Of Trustmentioning
confidence: 99%